UNDERSTANDING MUSLIM MILLENNIALS' FINANCIAL WELL-BEING THROUGH DAILY BEHAVIOR AND ISLAMIC ECONOMIC VALUES - Kurniawan, Heri; Bahjatulloh, Qi Mangku; Widyastuti, Emy; Mustofa, Nur Huri; Ariwoto, Muhamad Soliki; Yuliana, Dhea (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This qualitative study examines how everyday financial behaviors and Islamic economic values jointly shape the financial well-being (FWB) of Muslim millennials in the Special Region of Yogyakarta (DIY), Indonesia. Thirty participants (ages 25–44) completed semi-structured interviews supported by a closing checklist of 20 a priori indicators (daily behaviors and Islamic values) and the CFPB 10-item FWB scale. Data were analyzed using reflexive thematic analysis with a hybrid deductive–inductive codebook and descriptive matrices (e.g., BNPL × Present Security; Investing × Emergency Fund × Future Security). Findings indicate three reinforcing mechanisms. First, a “discipline bundle” (budgeting, regular saving, purchase delay, price comparison, thrifty promo use) intertwined with value-congruent practices (planned ZIS, amanah, prudence/iḥtiyāṭ, riba avoidance) strengthens current control and present security, aided by governed e-wallet/QRIS use (logs, caps, reminders). Second, capacity to absorb shock and future security are highest when regular investing coexists with ≥3-month emergency funds and is framed by tawakkul after prudent planning. Third, recurring active BNPL is consistently narrated with cash-flow strain and lower present security unless buffered by strong budgeting norms. Activation of syariah features is associated with psychological comfort and long-horizon commitment. Implications include value-aligned digital nudges (cooling-off timers, spending caps, goal-based saving, automated ZIS) and integrated Islamic/conventional financial-literacy programs for households, campuses, mosques, fintechs, and regulators. Limitations include a single-region, self-report, cross-sectional design; future work should adopt mixed-methods and longitudinal/experimental approaches.